2015
DOI: 10.1101/lm.038372.115
|View full text |Cite
|
Sign up to set email alerts
|

Transient relay function of midline thalamic nuclei during long-term memory consolidation in humans

Abstract: To test the hypothesis that thalamic midline nuclei play a transient role in memory consolidation, we reanalyzed a prospective functional MRI study, contrasting recent and progressively more remote memory retrieval. We revealed a transient thalamic connectivity increase with the hippocampus, the medial prefrontal cortex (mPFC), and a parahippocampal area, which decreased with time. In turn, mPFC-parahippocampal connectivity increased progressively. These findings support a model in which thalamic midline nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Thus, the unidirectional connection from hippocampus to mPFC may be reciprocated via routes through the thalamus. Indeed, a recent rodent study showed that the mPFC controls the excitability of hippocampal neurons via midline thalamic nuclei during fear memory encoding (Xu and S€ udhof, 2013), and in humans, it has been shown that midline thalamic nuclei mediate between mPFC and hippocampus during high-confidence memory retrieval (Thielen, Takashima, Rutters, Tendolkar, & Fern andez, 2015). Previous imaging studies have already shown that successfully and confidentially remembered associations lead to increased activation in hippocampal and medial prefrontal cortices during encoding (Sperling et al, 2003;Chua, Rand-Giovannetti, Schacter, Albert, & Sperling, 2004;Chua, Schacter, Rand-Giovannetti, & Sperling, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the unidirectional connection from hippocampus to mPFC may be reciprocated via routes through the thalamus. Indeed, a recent rodent study showed that the mPFC controls the excitability of hippocampal neurons via midline thalamic nuclei during fear memory encoding (Xu and S€ udhof, 2013), and in humans, it has been shown that midline thalamic nuclei mediate between mPFC and hippocampus during high-confidence memory retrieval (Thielen, Takashima, Rutters, Tendolkar, & Fern andez, 2015). Previous imaging studies have already shown that successfully and confidentially remembered associations lead to increased activation in hippocampal and medial prefrontal cortices during encoding (Sperling et al, 2003;Chua, Rand-Giovannetti, Schacter, Albert, & Sperling, 2004;Chua, Schacter, Rand-Giovannetti, & Sperling, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Previous clinical studies demonstrate that proper thalamic function is critical for memory formation and consolidation. In humans, damage to the thalamic nuclei, especially medial and anterior nuclei, causes severe memory deficits known as diencephalic amnesia [12][13][14][15][16][17] . While the neural circuitry of the effects of Shox2 expression on recognition memory are unclear, perhaps these effects occur via effects on TCN connections to retrosplenial cortex as suggested by the anatomical connectivity indicated in our study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of these oscillations caused by aberrant activity in the thalamic circuit is thought to play a role in many neuropathological conditions, including epilepsy [2][3][4] , autism [5][6][7] , and schizophrenia [8][9][10][11] . Furthermore, damage to thalamic nuclei, especially medial and anterior nuclei, causes severe memory deficits known as diencephalic amnesia [12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…The thalamus has been described as an important structure regarding mPFC-hippocampus “communication” during memory processes. Evidence from human imaging studies as well as animal data revealed that the mPFC-thalamus-hippocampus axis is strongly associated with memory encoding (Xu and Südhof, 2013) memory consolidation (Thielen et al, 2015) and memory retrieval (Aggleton and Brown, 1999; Davoodi et al, 2009, 2011; Aggleton et al, 2010; Loureiro et al, 2012). Here, we show for the first time, that engagement in aerobic physical activity is associated with increased activation and functional connectivity in the mPFC-thalamus-hippocampal axis when elderly learn new face-occupation associations.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomically, the hippocampus is strongly connected to prefrontal regions as medial prefrontal cortex (mPFC; Preston and Eichenbaum, 2013) which, in turn, have reciprocal connections to several thalamic nuclei that are indirectly or directly reciprocally connected to the hippocampus in monkey (Aggleton et al, 2011). Moreover, a recent fMRI study revealed functional connectivity between hippocampus, mPFC and thalamus during episodic memory retrieval in young adults (Thielen et al, 2015). Therefore, we hypothesize that face association learning (encoding) is associated with the hippocampal-thalamus-mPFC axis and that engagement in aerobic physical activity has a positive effect on activation and functional connectivity within this memory network.…”
Section: Introductionmentioning
confidence: 99%